Do health care providers give sufficient information and good counseling during ante-natal care in Lao PDR?: an observational study - Phommachanh, S; Essink, DR; Wright, EP; Broerse, JEW; Mayxay, M (BioMed Central, 2019)
Background: It is increasingly recognized that improving the quality of maternal health care delivery is of utmost importance in many countries. In Laos, the quality of antenatal care (ANC) service remains inadequate, but it has never been assessed thoroughly. This study aims to determine the ANC quality at the urban and rural public health facilities in Laos and provides suggestions to improve health education and counseling in addition to other routine care in public ANC services.